Pengaruh Perbedaan Strain Tilapia F5 (Larasati, Merah, Hitam) Yang Diberi Pakan Dengan Nilai E/P 10,96 Kkal/G Protein Terhadap Pertumbuhan Dan Kelulushidupan - Vardian, Ahmad Kurnia; Subandiyono, Subandiyono; Pinandoyo, Pinandoyo (Journal of Aquaculture Management and Technology, 2013)
The raising of needs of this fish followed by the increasing in quality of tilapia larval has resulted three hybrid tilapia fish strains. The differences in starins could change the nutritional requirement of those new strains. Because of that, appropriate commercial food was needed in order to maximize its growth. The aim of this experiment was to study the effects of tilapia (Oreochromis niloticus) strains on the response to the growth, survival rate and food conversion ratio on strains of tilapia seeds which was fed with 10,96 Kcal/gram protein foods. The purpose of this study was to give significant information about applying high quality tilapia fish strains and appropriate food in cultivating tilapia fish. The method used was completely randomized design with three treatments and four replicates, where the A treatment was Larasati strain fed on dietary E/P 10.96 kkcal/g protein; B treatment was the Red strain fed on dietary E/P 10.96 kkcal/g protein; and C treatment was the Black strain fed on dietary E/P 10.96 kkcal/g protein. The material used was 3 strains of tilapia which is Larasati, the Red and the Black. The result of the research showed that different strains of tilapia was significant effect to weight gain and long, but is not effect to efficiency feed utilization but and survival rate (P>0,05). The highest weight growth was found on Larasati strain which was (28,70±0,51%/day) of average weight growth, while the highest length growth was on Black strain which was (1,29±0,05%/day). The result rate was efficiency feed utilization (0.712±0.01% - 0.665±0,05%). The result for survival rate was (90,45±1,05 - 89,45±0,34). It was suggested The Effect of Differences F5-Tilapia Strain (Larasati, Red, Black) Fed on Dietary E/P 10,96 kcal/g Protein on its Growth and Survivors was able to significant effect RGRW and RGRLvalue.